Analisis Kritis Implementasi Kurikulum 2013 Dan Kurikulum Merdeka: Tantangan Dan Peluang Di Berbagai Jenjang Pendidikan - Trismayanti, Regina; Anandita, Putri Zahra; Alfarisi, Uday Salman (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This study aims to compare the implementation of the 2013 Curriculum and the Independent Curriculum in Indonesia's education system. The method used is a literature study by analyzing various academic sources related to curriculum policies, learning approaches, and their impact on the teaching and learning process. The results show that the 2013 Curriculum emphasizes a scientific approach and authentic assessment, while the Independent Curriculum focuses on flexibility in student-centered learning. Although the 2013 Curriculum has been widely implemented, challenges remain, such as teacher readiness and limited facilities. On the other hand, the Independent Curriculum provides greater freedom for teachers and students in determining learning methods and materials, but it still faces obstacles in resource readiness and equitable infrastructure. In conclusion, the comparison between the two curricula indicates a shift from a structured approach to a more flexible system, highlighting the need for continuous policy support to enhance the effectiveness of curriculum implementation in Indonesia.